(untitled) (Journal of the College of Languages (JCL), 2022)
Musicality is a fundamental feature of poetry that takes the interest of scholars and critics. Most poets rely on a variety of literary devices and techniques to bring music to their work like rhymes - words that appear at the end of lines in poetry - and on arranging words techniques in such a way to create a pseudo melody, which is achieved primarily by patterning (or repeating) certain sounds. Such a poetic rhetorical and verbal enhancer’s aspect represented ever since the beginning of the classical poetry has been manifested more evidently in Nali’s poetry. His poetry is marked with particular letters that have played a substantial role in the rhyming that rings like cymbals or jingle like internal elevated rhymes. Within a descriptive-analytical approach, the present study describes the musical techniques of Nali’s poetry, particularly of what is called letter poetry, and investigates the application of these letters as figures of rhetoric in Nali’s poetic style. The study traces the letter poetry types and its impacts on poetic meaning creation in the light of semantic framework. کورته مۆسیقای هۆنراوه هەر لە سەردەمانی کۆنەوه، گرنگییەکی تایبەتی پێدراوه و جێگەوپێگەیەکی ئەوتۆی له چوارچێوه و پەیەکەرەی شیعردا هەبووه. ئەم مۆسیقایه به ڕیزکردن و پاتبوونەوه و ڕێکخستنی وشە و پیته لێکچوو و هاوئاهەنگەکان پەیدا دەبێت. هەر له شیعری کلاسیکەوه تا ئەمڕۆ ئەم تەکنیکه له ڕازه و هونەره جۆربەجۆرەکانی ڕەوانبێژیدا خۆی نواندووه و دەرکەوتووه. له شیعری نالیدا به شێوازێکی زەق و بەرچاو پاتبوونەوەی پیتێکی دیاریکراو له هەندێ له هۆنراوەکانیدا دەورێکی مۆسیقایی بەهێز و زۆر دیاری به ئەستۆ گرتووه و ئاواز و مۆسیقای شیعرەکەی بەرزتر کردۆتەوه. به شێوەیەک که دەکرێت ناوی ئەو پیته ببڕین به سەر ئەو هۆنراوەدا و به «پیتەشیعر» ناوزەدی بکەین. ئەم توێژینەوە به شێوازی تەوسیفی – لێکۆڵینەوەیی هەوڵیداوه به خوێندنەوەی شیعرەکانی نالی هونەر و مۆسیقا و دەوری پیتەشیعر ڕوونبکاتەوه و وەک تەکنیک و هونەرێک له شێواز و شیعری نالیدا بیناسێنێت. له ئاکامدا توانیویه چەشن و کاریگەری و بەتایبەت لایەنە واتاییەکانی ئەم هونەره له شیعری نالیدا بخاته بەر چاو و تیشکی لێکۆڵینەوه و ڕاڤه و شرۆڤەیان لێبدات.